Barriers and Facilitators to Acceptability of the Female Condom in Low- and Middle-Income Countries: A Systematic Review - Luther-King Fasehun; Sarah Lewinger; Oyinlola Fasehun; Mohamad Brooks (Ubiquity Press, 2022)
Background: Sexually transmitted infections, including HIV, remain a significant public health challenge for low- and middle-income countries, and about 111 million unintended pregnancies occur in these countries annually. The female condom is the only commonly available method that affords women and girls more control in protecting themselves from sexually transmitted infections, as well as unintended pregnancies. Yet, the female condom only accounts for 1.6% of total condom distribution worldwide. Objectives: To help fill the gaps in an understanding of what works for improved acceptability and use of the female condom in low- and middle-income countries, we conducted a systematic review of the literature that focuses on acceptability of the FC, as examined in the specific settings of intervention programs or research in low- and middle-income countries. Methods: We conducted a preliminary search of two purposively selected databases (PubMed and POPLINE) for English language articles from 2009 to 2019 with the keyword "female condom." PubMed yielded 145 articles, while POPLINE yielded 164 articles. Included studies involve a purposive, interventional deployment of the female condom; have occurred in a low- or middle-income country, as defined by the World Bank; and have focused on acceptability of the female condom. Upon review of duplicates and abstracts, a total of 14 articles made the final selection. Findings: The included articles represent seven different countries: the Dominican Republic, El Salvador, China, Malaysia, Nicaragua, South Africa, and Uganda. We identified four key barriers to FC acceptability, including partner acceptability, functionality, aesthetics, and access. We identified four key facilitators to FC acceptability, including repeated use, supportive attitudes, protection confidence, and reproductive control. Conclusion: Effective promotion and uptake of the female condom in low- and middle-income countries can be realized if novel strategies and approaches are implemented to tackle persistent barriers to acceptability.